2005
DOI: 10.1111/j.1475-1313.2005.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Distance vergence adaptation is abnormal in subjects with convergence insufficiency

Abstract: It is well known that in convergence insufficiency (CI) prism adaptation is reduced in response to base-out (BO) prisms at near. There have also been some suggestions in the literature that adaptation is reduced at other distances as well. The present data show that in CI adaptation is not only reduced in response to BO at near, but also in response to base-in (BI) at near and for both BI and BO at distance. This raises the interesting question whether distance adaptation becomes reduced because of reduced nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Furthermore, the reduced vergence adaptive ability was not only demonstrated at near but also for far fixation. This observation is similar to the observation in CI subjects made by Brautaset and Jennings (2005b) and suggests that when adaptation is reduced it is a general reduction that affects both convergence and divergence at both far and near fixation. Schor and Horner's (1989) theory of unbalanced adaptation, ie, when accommodative adaptation is elevated vergence adaptation is reduced or vice versa, holds for CI.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the reduced vergence adaptive ability was not only demonstrated at near but also for far fixation. This observation is similar to the observation in CI subjects made by Brautaset and Jennings (2005b) and suggests that when adaptation is reduced it is a general reduction that affects both convergence and divergence at both far and near fixation. Schor and Horner's (1989) theory of unbalanced adaptation, ie, when accommodative adaptation is elevated vergence adaptation is reduced or vice versa, holds for CI.…”
supporting
confidence: 88%
“…According to their theory subjects with CI will have reduced vergence adaptation, a high CA/C ratio, elevated accommodative adaptation, and a low AC/A ratio. These suggestions for CI have been confirmed by Brautaset and Jennings (2005b;2006). Schor and Horner explained CE by reduced accommodative adaptation, high AC/A ratio, elevated vergence adaptation, and a low CA/C ratio.…”
Section: Introductionmentioning
confidence: 74%
“…Individuals differ in their heterophoria and it has been shown that heterophorias constantly adapt to different viewing conditions. 19,[57][58][59] Moreover, the heterophoria plays an important role in several vergence regulations and might affect, for example, pre-programmed aspects of vergence adjustments. [60][61][62] According to Jaschinski, 63 we would expect an exophoria for our present viewing distances and would argue that the overall exophoric status of the binocular system might contribute to the overall pattern of exophoric fixation disparities found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These data, along with neurophysiological evidence derived from primates (Mays, 1984;Mays & Gamlin, 1995;Nitta, Akao, Kurkin, & Fukushima, 2008) has provided the foundation for the hypothesis that disparity driven phasic divergence and convergence responses are controlled by separate neural substrates. The effects of stimulus direction on SV responses, on the other hand, remains unclear (Brautaset & Jennings, 2005;Sethi & North, 1987). In addition, recent evidence has indicated a strong relationship between peak velocity and shortterm sensorimotor adaptations within the PV mechanism (Alvarez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%